Integrating routine immunization into COVID-19 vaccination improve coverage but could create equity issues: evidence from Niger State, Nigeria - Hilary I. Okagbue; Akolade Jimoh; Olugbemisola Samuel; Hadley Ikwe; Saheed Isiaka; Irene Okoye; Joshua David; Zubair Adegoke (BMC Public Health)
Abstract Background Integrating Routine Immunization (RI) into COVID-19 vaccination implies that COVID-19 vaccination is the primary focus, with RI services added to the effort. During COVID-19 vaccination campaigns in Nigeria, healthcare workers also provided routine vaccines such as measles and polio to individuals who came for their COVID-19 shots. This paper aims to demonstrate that integrating RI into COVID-19 vaccination increases overall vaccine coverage but may introduce equity issues. Methodology The data used in this study consist of COVID-19 immunization records (first, second, and booster doses) from 23 local government areas (LGAs) in Niger State, Nigeria. The project aimed to vaccinate the remaining 30% of the population who had not received any COVID-19 vaccine doses. Two LGAs were excluded due to security concerns. Routine immunizations (RIs) provided alongside COVID-19 vaccinations included the inactivated polio vaccine (IPV), oral polio vaccine (OPV), pentavalent polio vaccine (PENTA), and other vaccines based on specific needs, primarily targeting zero-dose children. The primary outcome was vaccine coverage, measured as the percentage of targeted individuals who received at least one dose of the COVID-19 vaccine. Secondary outcomes included the uptake of routine immunization during COVID-19 vaccination campaigns and a gender equity analysis to assess disparities in vaccination rates between males and females. Results A total of 436,598 individuals were vaccinated, with a daily average of 3,898. Among those vaccinated, 49.78% were male, while 50.22% were female, achieving a percentage coverage of 101%. Of the vaccinated individuals, 76% received a single dose, 5.1% received a second dose, and 18.3% received a booster dose. Among those who received a single dose, 49.9% were male and 50.1% were female. Among those who received the second dose, 47.4% were male and 52.6% were female. Among those who received the booster dose, 49.8% were male and 50.2% were female. No significant mean differences were found between males and females for those who received the first and booster doses. Similarly, there were no significant mean differences between the targeted and achieved vaccinations, despite variations in coverage across the 23 LGAs. Additionally, 60,373 routine immunizations were administered alongside COVID-19 vaccinations. A breakdown of the RI distribution showed that 17.6% of recipients received PENTA, 18.3% received OPV, 17.6% received IPV, and 46.5% received other vaccines. A significant mean difference was observed between males and females when RI was integrated into COVID-19 vaccinations, suggesting a gender disparity. Conclusion Although integrating RI into COVID-19 vaccination efforts increased overall immunization coverage, the data suggest potential inequities, as a higher proportion of RI doses were administered to females. This finding highlights differences in vaccine access between males and females. Further research is needed to understand the impact of gender differences in RI integration and to promote equitable vaccination access for all.